2022
DOI: 10.3390/youth2010004
|View full text |Cite
|
Sign up to set email alerts
|

Coming Out Strategies on Social Media among Young Gay Men in Malaysia

Abstract: Social media have afforded many young gay men the opportunity to explore their identities and practice coming out. The ease of use and the anonymity that can be assumed online has enabled young gay men to come up with different strategies of self-disclosure in social media. The present study seeks to examine these strategies among young gay men in Malaysia, given the limited data on the social media experiences of gay men in the country. In-depth interviews were conducted with six young, gay-identified men to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a study conducted in Malaysia, the online patterns of being ‘Out and Proud,’ where complete disclosure is seen among gays, and patterns of ‘Out and discreet’/’Facebook closeted,’ where anonymity is maintained using online secret identities to explore the process of coming out was discussed. [ 76 ] The study reported several risks of living an anonymous online identity as the boundaries of age and ethical norms are bypassed, putting youths are higher risk of exploitation. [ 76 ] Few studies have also highlighted the potential advantages of CO in social media platforms (Facebook and Twitter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Malaysia, the online patterns of being ‘Out and Proud,’ where complete disclosure is seen among gays, and patterns of ‘Out and discreet’/’Facebook closeted,’ where anonymity is maintained using online secret identities to explore the process of coming out was discussed. [ 76 ] The study reported several risks of living an anonymous online identity as the boundaries of age and ethical norms are bypassed, putting youths are higher risk of exploitation. [ 76 ] Few studies have also highlighted the potential advantages of CO in social media platforms (Facebook and Twitter).…”
Section: Discussionmentioning
confidence: 99%
“…[ 76 ] The study reported several risks of living an anonymous online identity as the boundaries of age and ethical norms are bypassed, putting youths are higher risk of exploitation. [ 76 ] Few studies have also highlighted the potential advantages of CO in social media platforms (Facebook and Twitter). [ 77 , 78 ] However, there are safety concerns, too; these platforms can be both transformative and risky (disclosure can lead to bullying and humiliation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Twitter was chosen as the source of participants since it serves as a safe avenue for participants to disclose their sexual identities. Participants are able to discuss aspects of their personal lives, such as romances and lifestyles, more openly and freely on Twitter, and this is the reason the questionnaire was posted on it [18].…”
Section: Methodsmentioning
confidence: 99%
“…The main cause of selective visibility outside China is social pressure in general and ‘stigma related to heterosexism and homo-prejudice’ (Moe et al, 2011: 229) in particular. Partly because of this pressure, some queer users choose to disclose sexual orientation only to some of their friends on Facebook (Jerome and Hadzmy, 2022). Some of them only display that they are interested in LGBTQ+ activities on the homepage of their social media (Das and Farber, 2020).…”
Section: Playing Edge-ball and Selective Visibilitymentioning
confidence: 99%